Analisis Laju Paparan Radiasi Pada Daerah Kerja di Instalasi Kedokteran Nuklir RSUD Abdoel Wahab Sjahranie - Putri, Anisa; Zurma, Retno; Putri, Erlinda Ratnasari; Munir, Rahmawati (Progressive Physics Journal, 2023)
An analysis of radiation dose rate has been conducted by using surveymeter Inspector Sn.46685 in the working area of the Nuclear Medicine installation at Abdoel Wahab Sjahranie Hospital. This study aims to measure the rate of radiation exposure and conduct an evaluation based on the control of the work area. Data collection is carried out in the room in the Nuclear Medicine installation. The measurement results showed that the rate of radiation exposure in the working area of nuclear medicine installations ranged from 0.09-21.56 μSv per hour. The radiation exposure rate obtained is still classified as below 10 μSv/h, but in the waste chamber the measurement obtained is relatively high because it exceeds 10 μSv/h.